The Antecedants of Employee Loyalty in Family Business From Millenial Perspectives - Andreas Wijaya; Brendi Wijaya; Juan Carlos (DINASTI RESEARCH, 2020)
According to PWC (2015), almost 80% family businesses in Indonesia have non-working family member shareholders. Furthermore, Susenas (2017) projected millenial generation in next five years will increase significantly and reach the peak 34% of population. To cope these challanges, executives need adoption process to become more professional in business operations while recruiting and retaining qualified employees. This research aim to measure the antesedan of family business for instance; organization culture, empoloyee engagement ,ogranizational justice, loyalty. Sample was collected as much 288 selected through purposive sampling method in order to given closed questionarries using likert scale. As a result, organizational culture had impact to employee engagement whereas organizational culture not affected organizational justice, Therefore employee engagement and organizational justice has affected employee loyalty respectivly. Moreover this research reflect new horizons, such as: work autonomy, flexible work arrangements to finding new study of millenial behaviour while HR recuruiting or maintaining employee